2017
DOI: 10.1371/journal.pone.0169593
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Versus Central Laboratory Measurements of Hemoglobin, Hematocrit, Glucose, Bicarbonate and Electrolytes: A Prospective Observational Study in Critically Ill Patients

Abstract: IntroductionRapid detection of abnormal biological values using point-of-care (POC) testing allows clinicians to promptly initiate therapy; however, there are concerns regarding the reliability of POC measurements. We investigated the agreement between the latest generation blood gas analyzer and central laboratory measurements of electrolytes, bicarbonate, hemoglobin, hematocrit, and glucose.Methods314 paired samples were collected prospectively from 51 critically ill patients. All samples were drawn simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 37 publications
(36 reference statements)
3
46
1
Order By: Relevance
“…In these result pairs, the laboratory‐based Hb measurement tends to indicate blood transfusion 3‐4 times more frequently than BGA. This overestimation by BGA has been observed in previous studies …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In these result pairs, the laboratory‐based Hb measurement tends to indicate blood transfusion 3‐4 times more frequently than BGA. This overestimation by BGA has been observed in previous studies …”
Section: Discussionsupporting
confidence: 83%
“…This overestimation by BGA has been observed in previous studies. 19 The blood glucose had small bias and limits of agreement; however, there were two observations of concern. Firstly, 7.1% of readings by the two methods were outside the US-CLIA variability limits, and secondly, the difference between the BGA and AA increased above 10 mmol, with BGA tending to overestimate blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a 2017 publication investigating the comparability of a blood gas analyser to the central laboratory method concluded that the methods could not be used interchangeably for Hb measurement where Clinical Laboratory Improvement Amendments of 1988 proficiency testing criteria (Centers for Medicare & Medicaid Services, ) was used to define interchangeability. The authors reported that Hb was systematically overestimated by the BGA by a mean of 8 g/l (Allardet‐Servent et al , ).…”
Section: Range Of Equipment and Assaysmentioning
confidence: 99%
“…With regard to Hct, the Siemens RAPIDPoint (Siemens, Germany) POC system demonstrated a bias of −1.1 compared with the reference value. [9] In this study, nurses who were trained on the rapid point system performed the test in critically ill patients. Another POC instrument, the haemocytometer, was evaluated in an intensive care setting.…”
Section: Researchmentioning
confidence: 99%